ANALISIS MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) PADA PTKI UIN IMAM BONJOL PADANG - Nola Ariesta Elvan; Yusnil Khoiriah Siregar; Muhammad Zalnur; Muhammad Kosim (Program Studi Manajemen Pendidikan Islam, 2025)
This study aims to analyse the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy at Imam Bonjol State Islamic University (UIN) Padang as part of the State Islamic Religious Universities (PTKIN). This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The results showed that the implementation of MBKM at UIN Imam Bonjol Padang is still limited to the administrative level. Student exchange programmes abroad have not been implemented, internship programmes across departments have not been structured, and there are a number of obstacles such as differences in regulations between institutions, unsynchronised course offerings, low student interest, and lack of information and socialisation. Although there is a policy framework and cooperation documents between PTKIN, the implementation is still not optimal. This study recommends the need to strengthen socialisation, harmonise regulations, and actively involve the entire academic community to support the success of the MBKM program at PTKIN.